2014
DOI: 10.1590/s1516-8913201402582
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Alterations in Common Carp (Cyprinus carpio L.) Gills Caused by Thiamethoxam

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
5
6
0
Order By: Relevance
“…In fact, after exposure to the low-tested concentration, the more frequently detected alteration is an intense proliferation of primary epithelium. A similar response has been observed in several teleost species after exposure to a wide variety of pollutants, including organophosphorus compounds (OPs) [37,[40][41][42][43][44], thus suggesting the conservative nature of this trait. In fact, the increase in epithelial thickness allows the gills to mechanically prevent the uptake of unwanted substances.…”
Section: Morphological Alterationssupporting
confidence: 62%
See 1 more Smart Citation
“…In fact, after exposure to the low-tested concentration, the more frequently detected alteration is an intense proliferation of primary epithelium. A similar response has been observed in several teleost species after exposure to a wide variety of pollutants, including organophosphorus compounds (OPs) [37,[40][41][42][43][44], thus suggesting the conservative nature of this trait. In fact, the increase in epithelial thickness allows the gills to mechanically prevent the uptake of unwanted substances.…”
Section: Morphological Alterationssupporting
confidence: 62%
“…Each slide has been observed at different magnifications (20×, 40×, 100×) to unveil any alterations. The degree and extent of alterations were assessed using the appropriately modified grading system of Georgieva and colleagues [ 40 ]. The grading system was: (−) no histological alterations; (+/−)-mild histopathological alterations; (+) moderate histopathological alterations; (++) severe histopathological alterations; (+++) very severe histopathological alterations of the gill surface architecture.…”
Section: Methodsmentioning
confidence: 99%
“…The present study found aneurysms, which actually were not observed in the common carp gills when it was exposed to thiamethoxam. This result indicated that the test fungicide was more toxic to the fish compared to the insecticide as reported previously (Georgieva et al 2014). The study not only focused on the histological alterations in the gill structure but also provided the degree of expression of each histological change, which was caused by the fungicide in order to establish more precisely the degree of its toxic effects.…”
Section: Resultssupporting
confidence: 87%
“…The most severe changes in the blood circulatory systemaneurysms, were more pronounced compared to the other tested fungicide concentrations (Table 1, Fig. 1) as reported earlier by (Georgieva et al 2014), the present study showed proliferative and degenerative changes in the fish gill structure. However, in the present study a fungicide was used at different concentrations, but not an insecticide.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation